Pest Identification Guide: Bondar’s Nesting Whitefly: Paraleyrodes bondari - Nicole A Casuso; Hugh A. Smith (EDIS)
Bondar’s nesting whitefly (Paraleyrodes bondari) is an emerging pest in Florida that targets ficus species, hibiscus, sugar apple, guava, and citrus, among others. Learn to identify these tiny flies with this handy, 2-page guide written by Nicole A. Casuso and Hugh A. Smith and published by the UF/IFAS Entomology and Nematology Department. https://edis.ifas.ufl.edu/in1204